Comprehensive clinical insights to diabetic retinopathy in Pakistan: examining prevalence, identifying risk factors, and analyzing visual health patterns - Saeed, Umar (International Journal of Pathology, 2023)
Background: Diabetes is a significant risk factor for diabetic retinopathy (DR), with a notably high incidence in Pakistan. We conducted a comprehensive study with 629 participants to explore DR prevalence, distribution, and its associations with various factors.Methods: A multicenter cross-sectional study was conducted from January to July 2023 in collaboration between International Center of Medical Sciences Research (ICMSR) and the Research and Development Department at Islamabad Diagnostic Center (IDC).Study enrolled 629 male and female diabetic patients who underwent prior fundoscopic examination. Data were collected using a non-probability consecutive sampling method, with skilled investigators after ethical approval from ICMSR and IDC review boards respectively.Results: Among male patients, 18% exhibited no retinopathy, 25.2% had proliferative diabetic retinopathy (PDR), and 27.3% displayed non-proliferative diabetic retinopathy (NPDR). Among female 8.5% had PDR, 13.2% NPDR, and 10.2% no retinopathy. Urban patients showed 35.4% PDR, 32.2% NPDR, and 29%no retinopathy. Rural patients displayed 37.5% NPDR, 23% PDR, and 17.7% no retinopathy. PDR was notably higher in urban areas. Patients with diabetes for over a decade had higher PDR prevalence (40.4%) than those with <10 years (62% NPDR).Study revealed that 33% of oral hypoglycemic medication users had PDR, while 40.6% of patients had NPDR. Family history of diabetes correlated with 37.2% PDR and 42.45% NPDR. Hypertension was present in 61.5% of PDR and 41.2% had NPDR, history of smoking linked to 43.8% NPDR and 38.7% PDR. Notably, PDR was more prevalent in patients with a history of diabetic foot (19.07%). Among clinically significant macular edema patients, 25.6% had no retinopathy, 69.5% had NPDR, and 37.8% had PDR.Conclusion: Early detection and management is critically important particularly for individuals with specific risk factors. Healthcare practitioners should prioritize targeted interventions and comprehensive management to prevent vision loss and enhance visual health in diabetes patients